The monkey king - Dickins, Rosie (Usborne Pub Ltd; UK, 2007)
A boastful monkey king is given a job by the Emperor of Heaven in an attempt to keep him from bothering people, but when he ruins the Empresses' peach banquet, Buddha teaches him a lesson.